3D structure aerogels constructed by reduced graphene oxide and hollow TiO2 spheres for efficient visible-light-driven photoreduction of U(vi) in air-equilibrated wastewater. Issue 8 (15th July 2021) - Dong, Zhimin; Zhang, Zhibin; Li, Zifan; Feng, Yue; Dong, Wenjie; Wang, Ting; Cheng, Zhongping; Wang, Youqun; Dai, Ying; Cao, Xiaohong; Liu, Yuhui; Liu, Yunhai
Abstract : A novel 3D structure composite aerogel was constructed by nanostructured hollow TiO2 and RGO with excellent photocatalytic reduction activity for U(vi ) and reusability, evidencing the potential practical applications in environmental remediation. Abstract : Photocatalysis-assisted transition of uranium from the soluble U(vi ) to the insoluble U(iv ) is an efficient strategy for eliminating uranium. Herein, a novel 3D structure composite aerogel (3D RGO@TiO2 ) was applied to photoreduction of U(vi ) under visible light. The introduction of RGO could expand the light absorption region and facilitate efficient charge separation of 3D RGO@TiO2 . Therefore, 3D RGO@TiO2 -3 (where the mass ratio of GO and H-TiO2 was 1 : 1) achieved the greatest U(vi ) reduction rate (0.03752 min −1 ) that is almost five times higher than that of RGO. Meanwhile, the reaction between photogenerated electrons and superoxide radicals ˙O2 − played the dominant role in reducing U(vi ) to (UO2 )O2 ·2H2 O in air-equilibrated wastewater. This study not only provides new insights into remediation of the radioactive environment but also proves the application prospect of the 3D RGO@TiO2 in the photocatalytic field.